SITUATIONAL LEADERSHIP OF SCHOOL PRINCIPALS BASED ON LOCAL WISDOM VALUES TO ENHANCE TEACHER PERFORMANCE - Yumeng Yunggin; Juharyanto Juharyanto; Ahmad Nurabadi (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to analyze the situational leadership of school principals based on local wisdom values bopakot (deliberation), kadangan (mutual cooperation), hormat daulun muntuo (mutual respect), and semangat dangan gari (sense of kinship) in improving teacher performance at SDN 001 Tana Tidung. The main focus of the study is how the principal adapts leadership styles to teachers’ characteristics, situational conditions, and local cultural values that serve as the foundation for building teachers’ professionalism and work ethic. This research employs a qualitative approach with a case study design, utilizing in-depth interviews, observations, and documentation studies. Data analysis follows an interactive model consisting of data reduction, data display, and conclusion drawing or verification. The findings indicate that the principal implements a flexible leadership model by integrating local values such as bopakot, kadangan, hormat daulun muntuo, and semangat dangan gari. This strategy has a positive impact on enhancing teachers’ motivation, discipline, and instructional quality. In conclusion, situational leadership grounded in local wisdom is proven to be effective in strengthening teacher performance while simultaneously preserving the cultural identity of SDN 001 Tana Tidung.